2014
DOI: 10.3122/jabfm.2014.05.140014
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Family-Centered Birth With Gentle Cesarean Delivery

Abstract: Purpose: In this commentary we describe our experience developing a "gentle cesarean" program at a community hospital housing a family medicine residency program. The gentle cesarean technique has been popularized in recent obstetrics literature as a viable option to enhance the experience and outcomes of women and families undergoing cesarean delivery.Methods: Skin-to-skin placement of the infant in the operating room with no separation of mother and infant, reduction of extraneous noise, and initiation of br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 20 publications
0
34
0
Order By: Relevance
“…6,7) No increases in maternal or neonatal complications were found, including surgical site infections, maternal blood loss, requirement for blood transfusions, or any neonatal parameters. One study 7) showed a shorter time to hospital discharge (4.0 vs. 4.4 days, P < 0.001) with the gentle cesarean vs. a traditional cesarean, and fewer instances of hospitalization more than 4 days (17% vs. 30%, P < 0.001).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…6,7) No increases in maternal or neonatal complications were found, including surgical site infections, maternal blood loss, requirement for blood transfusions, or any neonatal parameters. One study 7) showed a shorter time to hospital discharge (4.0 vs. 4.4 days, P < 0.001) with the gentle cesarean vs. a traditional cesarean, and fewer instances of hospitalization more than 4 days (17% vs. 30%, P < 0.001).…”
mentioning
confidence: 93%
“…2,3) The "gentle", or "family centered" cesarean delivery is an approach to operative delivery that reduces the emphasis on surgical rituals and processes and increases the clinical focus on the mother, the baby and the family. [4][5][6][7] The change in perspective celebrates the momentous birth event and encourages early motherinfant bonding. This concept has also become known as "kangaroo care", owing to the methods that marsupial animals use in the early care of their young.…”
mentioning
confidence: 99%
“…7 In America, family-centered "gentle caesarean" programmes enable mothers to have skin-to-skin contact during surgery. 13 Hospitals in Europe have developed nursing intervention protocols to minimise mother-infant separation after caesarean births. 14 These programmes have been shown to positively affect maternal-infant interaction and breast feeding initiation after caesarean delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the baby is placed immediately with the mother to provide early skin-to-skin contact [8]. Despite a lack of studies investigating the safety and true benefit of such an approach, more and more hospitals are implementing (a variation on) this technique [9,10].…”
Section: Introductionmentioning
confidence: 99%